2008
DOI: 10.1111/j.1399-0012.2008.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary health care personnel faced with cadaveric organ donation: a multicenter study in south‐eastern Spain

Abstract: PHC personnel have a favorable attitude toward donation, especially physicians, although it would be useful to provide more information to PHC personnel. Physicians could be a key element in the direct and indirect promotion of donation and transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 19 publications
5
24
2
1
Order By: Relevance
“…[24][25][26] Most studies that have examined this matter of brain death knowledge have shown a close association between the knowledge and acceptance of the concept of brain death and attitude toward organ donation and transplantation. 7,9,17,18,27 However, in this study, this association was not found. It is possible that the lack of awareness about this matter, in which only 25% of those surveyed accepted that it means a person's death, can account for these data.…”
Section: Antonio Ríos Et Al/experimental and Clinical Transplantationcontrasting
confidence: 53%
See 1 more Smart Citation
“…[24][25][26] Most studies that have examined this matter of brain death knowledge have shown a close association between the knowledge and acceptance of the concept of brain death and attitude toward organ donation and transplantation. 7,9,17,18,27 However, in this study, this association was not found. It is possible that the lack of awareness about this matter, in which only 25% of those surveyed accepted that it means a person's death, can account for these data.…”
Section: Antonio Ríos Et Al/experimental and Clinical Transplantationcontrasting
confidence: 53%
“…There is a clear relation between this fear and the discovery of brain death. [14][15][16][17][18] Studies of the Spanish population have shown that the lack of understanding of the brain death concept and the fear of apparent death in the donation process was at one point as high as 70% to 80%. 19 Although these data have improved, presently, nearly 50% of the Spanish population do not know this concept, and its misconception continues to be an independent factor affecting attitude toward deceased organ donation.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8 The following representatives in each service were contacted to distribute the questionnaires: the head of service for the physicians' questionnaires, the nursing coordinator for the nursing personnel, and an administrator for non-health care personnel, who were each given an explanation of the study and were made responsible for distributing the survey in selected shifts. The questionnaire was completed anonymously and was self-administered in 3 to 5 minutes.…”
Section: Opinion Survey and Study Variablesmentioning
confidence: 99%
“…Unlike the situation in attitude toward deceased organ donation 20,21 no differences have been found in terms of job category or other variables of this nature, but they have emotional and other factors related directly or indirectly with donation and transplantation. 22,23 As shown in Table 2, a favorable attitude toward deceased organ donation is a factor which encourages a positive attitude toward living donation.…”
Section: Discussionmentioning
confidence: 86%